2016
DOI: 10.1038/srep27964
|View full text |Cite
|
Sign up to set email alerts
|

Disorganized cortical thickness covariance network in major depressive disorder implicated by aberrant hubs in large-scale networks

Abstract: Major depressive disorder is associated with abnormal anatomical and functional connectivity, yet alterations in whole cortical thickness topology remain unknown. Here, we examined cortical thickness in medication-free adult depression patients (n = 76) and matched healthy controls (n = 116). Inter-regional correlation was performed to construct brain networks. By applying graph theory analysis, global (i.e., small-worldness) and regional (centrality) topology was compared between major depressive disorder pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 70 publications
2
25
2
Order By: Relevance
“…The unique neuroimaging pattern that distinguished ELS involved the ICC, medial OFC, and insula, with the strongest post hoc predictive value in the medial OFC. This cluster of regions has been previously associated with negative affect and self‐referential processing, which is consistent with a higher degree of emotional dysregulation observed in the ELS + group.…”
Section: Discussionsupporting
confidence: 87%
“…The unique neuroimaging pattern that distinguished ELS involved the ICC, medial OFC, and insula, with the strongest post hoc predictive value in the medial OFC. This cluster of regions has been previously associated with negative affect and self‐referential processing, which is consistent with a higher degree of emotional dysregulation observed in the ELS + group.…”
Section: Discussionsupporting
confidence: 87%
“…[28][29] The unique neuroimaging pattern that distinguished ELS involved the ICC, medial OFC, and insula, with the strongest post hoc predictive value in the medial OFC. This cluster of regions has been previously associated with negative affect and self-referential processing, 30 which is consistent with a higher degree of emotional dysregulation observed in the ELS + group.…”
Section: Discussionsupporting
confidence: 86%
“…A few studies have reported significant alterations in global network architecture measures in individuals with various psychiatric disorders, particularly MDD. For example, lower small-worldness and clustering coefficient measures have been reported in MDD (Long et al, 2015; T. Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%